Secondhand Smoke and Socio-Demographic Associated Factors: Results From the Vietnam Population-Based Provincial Global Adult Tobacco Survey in 2022 - Le Thi Thanh Huong; Tran Thi Tuyet Hanh; Le Tu Hoang; Phan Van Can; Thang Nguyen-Tien; Nguyen Quynh Anh; Phan Thi Thu Trang; Nguyen Thi Huong; Dao Le Hoang Minh; Luong Ngoc Khue; Phan Thi Hai; Nguyen Thuy Linh; et al. (Tobacco Use Insights, 2024)
Background: Secondhand smoke (SHS) has detrimental effects on community health, including coronary heart diseases, stroke, lung cancer etc. This manuscript exploited data from the Vietnam Population-based Provincial Global Adult Tobacco Survey (PGATS) in 2022 to update the prevalence of adult exposure to SHS and associated socio-demographic factors. Methods: With the sample size of 71,981 adults aged 15+ throughout 30 provinces and cities in Vietnam, data was collected using the Global Adult Tobacco Survey (GATS) questionnaire. Bivariate analysis and multivariate logistic regression modelling were performed. Results: In the past 30 days, 44.4% (95% CI: 44.0%-44.9%) adults aged 15+ exposed to SHS at home while 23.1% (95% CI: 22.6%-23.6%) exposed to SHS at work. Female exposure to SHS in the past 30 days was higher at homes but lower at indoor workplaces. Participants aged 15-24 were likely to have higher odds of SHS exposure in the past 30 days to other age groups. Those living in the urban areas had 1.15 times higher odds (95% CI: 1.08-1.22) of exposure to SHS than those in the rural areas. Current smokers tended to have 2.2 times higher odds of exposure to SHS at the indoor workplaces compared to non-smokers (95% CI: 2.05-2.37). Conclusions: The prevalence of exposure to SHS at home was still relatively high amongst the adult population. While there was a significant reduction of SHS exposure at indoor workplaces, there was a higher prevalence of women being exposed to SHS at home. The Government of Vietnam should continue to strictly implement the smoke-free environment resolution at indoor workplaces and appropriate communication campaigns to protect people, especially women from SHS exposure at homes.